Atomic Particles and Atom Systems Data for Properties of Atomic Objects and Processes - Smirnov, Boris M. (Springer Series on Atomic, Optical, and Plasma Physics,, 2018)
This book presents physical units and widely used physical formulas, which are given together with conversion factors in various units. It includes frequently used atomic spectra and data for atoms, ions and molecules, as well as potential curves for diatomic molecules, and provides numerical parameters for transport phenomena in gases and plasmas. Further, the rate constants of a number of processes in atmospheric ionized air have been added to this second edition of the book. The numerical data has been selected from the information on atoms, atomic systems, atomic processes and models for atomic physics in this area, and the numerical parameters of atoms, ions and atom systems are included in periodical tables of elements.